Pharmacokinetics and safety evaluation of anemoside B4 in healthy Beagle dogs - Ji, Jinzhao; Ma, Yuqiao; Wan, Shaobing; Ding, Xiaoqing; Wang, Jingyu; Zhong, Yongcheng; Song, Yangyang; Zhao, Junqing; Su, Zhetong; Jia, Kun; Li, Shoujun (Frontiers in Veterinary Science, 2025)
BackgroundAnemoside B4 (AB4), a pentacyclic triterpenoid saponin extracted from the traditional Chinese medicinal herb Pulsatilla chinensis, has shown anti-inflammatory and immunomodulatory effects in both preclinical and clinical studies. However, pharmacokinetic and safety data in dogs remain limited. This study aimed to evaluate the pharmacokinetics, bioavailability, and safety of AB4 in healthy Beagle dogs.MethodsIn the single-dose pharmacokinetic study, 40 dogs received subcutaneous AB4 at 10, 20, or 40 mg/kg, or an intravenous bolus at 20 mg/kg. Plasma concentrations were measured using a validated HPLC–MS/MS method to determine pharmacokinetic parameters, bioavailability, dose proportionality, and sex-related differences. In the repeated-dose study, 10 dogs received 20 mg/kg subcutaneously once daily for 7 consecutive days to evaluate drug accumulation and fluctuation. In the target animal safety study, 32 dogs were randomly assigned to receive 1× (20 mg/kg), 3× (60 mg/kg), or 5× (100 mg/kg) doses of AB4, and saline as a control, via daily subcutaneous injection for 7 days. Routine clinical examinations, hematology, serum biochemistry, gross necropsy, and histopathology were assessed.ResultAB4 exhibited rapid elimination, high absolute bioavailability, and dose-proportional pharmacokinetics in the 10–40 mg/kg range. No evidence of accumulation after repeated dosing. Within the dose range of 20–100 mg/kg, AB4 demonstrated good safety, with no observable toxicity or adverse effects. No significant effects were observed on physiological parameters. Histopathological analysis revealed no consistent or target-organ specific lesions.DiscussionThese findings provide fundamental pharmacokinetic and safety data to support the rational clinical use of AB4 in veterinary medicine and lay the groundwork for future clinical applications.